2015
DOI: 10.1071/bt14207
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary survey of the diversity of soil algae and cyanoprokaryotes on mafic and ultramafic substrates in South Africa

Abstract: Despite a large body of work on the serpentine-substrate effect on vascular plants, little work has been undertaken to describe algal communities found on serpentine soils derived from peridotite and other ultramafic rocks. We report a preliminary study describing the occurrence of algae and cyanoprokaryotes on mafic and ultramafic substrates from South Africa. Results suggest that slope and aspect play a key role in species diversity and community composition and, although low pH, nutrients and metal content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Such investigations will likely reveal species that are endemic to the substrate or show a high affinity to ultramafic soils, as shown for such research conducted in South Africa (Venter et al 2015) and California, USA (Rajakaruna et al 2012). …”
Section: Discussionmentioning
confidence: 91%
“…Such investigations will likely reveal species that are endemic to the substrate or show a high affinity to ultramafic soils, as shown for such research conducted in South Africa (Venter et al 2015) and California, USA (Rajakaruna et al 2012). …”
Section: Discussionmentioning
confidence: 91%
“…For example, Oline (2006) found little evidence that there is a unique ultramafic-soil bacterial flora. Venter et al (2015) examined soil algae and cyanoprokaryotes in ultramafic and non-ultramafic soils in South Africa and reached a similar conclusion, but did discover that some species were unique to the ultramafic communities. In a review produced from the 2011 conference, Southworth et al (2014) found little evidence that mycorrhizal fungal communities are edaphically specialised.…”
Section: Ecology and Biogeography (Session 3)mentioning
confidence: 78%
“…BSCs can be tolerant of harsh environments such as extreme temperatures, drought (Belnap 2006) and heavy metals (Orlekowsky et al 2013). BSCs are also found on serpentine soils (Venter et al 2015), that are usually rich in magnesium and poor in calcium, with low nutrient and high heavy metal concentrations (Alexander et al 2007;Rajakaruna et al 2009). Cyanobacteria and algae make up a large component of BSCs and Venter et al (2015) found typical cyanobacteria and soil algae such as Leptolyngbya, Microcoleus, Phormidium, Chlamydomonas, Chlorococcum and Hantzchia in serpentine as well as non-serpentine soils but algae such as Chroococcus sp., Scytonema ocellatum, Nostoc linckia, Chlorotetraedron sp., Hormotilopsis gelatinosa, Klebsormidium flaccidum, Pleurococcus sp.…”
Section: Introductionmentioning
confidence: 99%